Care-related quality of life and care burden among caregivers of elderly trauma patients - Minoo Arjmand; Yousef Veisani; Arman Azadi (Archives of Trauma Research)
Background: Caring for elderly individuals with trauma presents a unique set of challenges that can place a substantial burden on caregivers, often leading to a decline in their quality of life over time.Objectives: This study aims to determine and compare the quality of life and care burden in caregivers of elderly trauma patients before and three months after discharge.Methods: This cross-sectional descriptive study was conducted on 120 caregivers of elderly patients from October to December 2021, using a convenience sampling method. Data were collected using the Brouwer Quality of Life Questionnaire (2006) and the Zarit Caregiver Burden Scale (1980). Data analysis was performed using SPSS version 23.Results: Findings indicated that caregivers reported a moderate level of quality of life. Care burden increased three months post-discharge, although it remained within the moderate range. Certain characteristics of the caregivers, such as the presence of illness, had a significant relationship with their quality of life. Factors such as gender, location and number of traumas, and history of illness were significantly associated with caregiver burden. However, no significant differences in quality of life or care burden were found based on age, education, or income levels.Conclusion: Caregivers of elderly trauma patients experience considerable care burden and a decline in quality of life during the caregiving period. Targeted educational and supportive interventions are essential to address caregivers’ needs and improve their well-being.